Increasing public support for supervised injection facilities in Ontario, Canada. (10th March 2014) - Strike, Carol; Jairam, Jennifer A.; Kolla, Gillian; Millson, Peggy; Shepherd, Susan; Fischer, Benedikt; Watson, Tara Marie; Bayoumi, Ahmed M.
Abstract Aim To determine the level and changes in public opinion between 2003 and 2009 among adult Canadians about implementation of supervised injection facilities (SIFs) in Canada. Design Population‐based, telephone survey data collected in 2003 and 2009 were analysed to identify strong, weak, and intermediate support for SIFs. Setting Ontario, Canada Participants Representative samples of adults aged 18 years and over. Measurements Analyses of the agreement with implementation of SIFs in relation to four individual SIF goals and a composite measure. Findings The final sample sizes for 2003 and 2009 were 1212 and 968, respectively. Between 2003 and 2009, there were increases in the proportion of participants who strongly agreed with implementing SIFs to: reduce neighbourhood problems (0.309 versus 0.556, respectively); increase contact of people who use drugs with health and social workers (0.257 versus 0.479, respectively); reduce overdose deaths or infectious disease among people who use drugs (0.269 versus 0.482, respectively); and encourage safer drug injection (0.213 versus 0.310, respectively). Analyses using a composite measure of agreement across goals showed that 0.776 of participants had mixed opinions about SIFs in 2003, compared with only 0.616 in 2009. There was little change among those who strongly disagreed with all SIF goals (0.091 versus 0.113 in 2003 and 2009, respectively). Conclusions Support for implementation of supervised injection facilities in Ontario, Canada increased between 2003 and 2009, but at both time‐points a majority still held mixed opinions.